New species and new records of Tingidae (Hemiptera. Heteroptera) from Thailand - Guilbert, Eric; Guidoti, Marcus (Zootaxa, 2018)
Eight species new to science are described from Thailand and 35 species new to Thailand are recorded. The fauna of Thailand, represented formerly by 12 species is increased to 52 species here. Comments on their distribution are added. Most of the species recorded come from material collected in the mid XXth century and deposited in Museums and from recent collecting surveys.